Estimation of Genetic Diversity in Lentil Germplasm - Alam, A. K. M. M.; Podder, R.; Sarker, A. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
The experiment was to determine the relationship between yield and yield contributing traits and select the promising genotypes. Twenty two genotypes and two check varieties were evaluated at Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during Rabi season, 2008-2009 in a RCBD with three replications. Significant variation among the lentil genotypes were observed in respect of days to first flowering, days to maturity, plant height, pod/plant, 100-seed weight and yield. The genotype BLX-02009-06-3 flowered and matured earlier. Among the test entries, BLX- 02009-18-3 and BLX-02009-18-1 were tall. The highest number of pod per plant was obtained in BLX-02009-04-5. The large seed size was found in LR9-130 and LR9-25. The highest yield was found in BLX-02009-04-1 followed by BLX- 02009-04-5 than the two check varieties. Difference between genotypic coefficient of variation and phenotypic coefficient of variation was small for the traits as plant height, days to maturity, days to first flowering and 100-seed weight. Among different traits, grain yield had high variation both at genotypic and phenotypic level due to the differences of genetic materials and also the differences of the environment. Grain yield was found to be positively and significantly correlated with plant height, pods/plant, 100-seed weight at genotypic and phenotypic levels.Keywords : Lentil, genetic diversity and PCA